Triboelectric Nanogenerator Based on Biowaste Tribopositive Delonix Regia Flowers Powder. Issue 12 (26th October 2022) - Patil, Swapnil R.; Chougale, Mahesh Y.; Kim, Jungmin; Shaukat, Rayyan Ali; Noman, Muhammad; Saqib, Qazi Muhammad; Khan, Muhammad Umair; Dongale, Tukaram D.; Bae, Jinho
Abstract : Sustainable energy harvesting technologies for maintaining the social ecosystem are predominantly addressing global challenges. Nowadays, non‐toxic and low‐cost energy‐generating nature materials are getting great attention for the development of flexible triboelectric nanogenerators (TENGs). Herein, Delonix regia flowers (DRFs) derived biowaste‐based tribopositive material are used to develop the high‐performance triboelectric nanogenerator. DRFs have the presence of carbonyl, hydroxyl, and amino acids functional groups, which plays a key role to demonstrate the electron‐donating ability of the DRFs. The proposed DRFs/PTFE device with a 20 cm 2 size and 6 mm separation distance exhibits a higher performance of voltage (655 V), current (59 μA), and instantaneous power (220.2 μW cm −2 ) under uniform external stress at 10 Hz frequency by air cylinder motor. It has also investigated the performance of the different device sizes and the spacing effect between triboelectric layers. The DRFs/PTFE‐structured TENG exhibits excellent ability to lit up the 210 light emitting diodes and run up the low‐power electronic stopwatch. According to the presented results, DRFs could be a superior candidate for triboelectric nanogenerator applications. Abstract : The energy crisis and environmental pollution are largely attending challenges across the globe. Herein, the Delonix regia flowers for the triboelectric nanogenerator are developed. The proposed device exhibits excellent performance in self‐powering devices, which concludes that the proposed work paves the path toward sustainable electronic technology.